2017
DOI: 10.1111/scs.12518
|View full text |Cite
|
Sign up to set email alerts
|

Nursing roles and functions addressing relatives during in‐hospital rehabilitation following stroke. Care needs and involvement

Abstract: Nurses experience their roles and functions addressing relatives after stroke as crucial, challenging and multifaceted. They acknowledged care needs of the relatives in their own right by addressing the relatives' vulnerability during in-hospital rehabilitation characterised by an existential threat to the physical as well as the shared life. The focus on the needs of relatives considering their expected future role was experienced as conflicting with restricting time frames and a healthcare system focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…Based on the experiences of healthcare professionals, family and carers played at most a supporting role in stroke care competence (O'Halloran et al, 2010). Other studies indicated that family and carers enhance patient care by providing information and helping to express the patient's needs (Aadal et al, 2018; Christiansen et al, 2017; Dreyer et al, 2016; Longley et al, 2018). On the other hand, challenges in co‐operation with relatives required healthcare professionals to adopt a range of different strategies (Christiansen et al, 2017), and there was a risk that dealing with patients' relatives could be perceived a stressful task in itself (Aadal et al, 2018) that shifts focus away from the patient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the experiences of healthcare professionals, family and carers played at most a supporting role in stroke care competence (O'Halloran et al, 2010). Other studies indicated that family and carers enhance patient care by providing information and helping to express the patient's needs (Aadal et al, 2018; Christiansen et al, 2017; Dreyer et al, 2016; Longley et al, 2018). On the other hand, challenges in co‐operation with relatives required healthcare professionals to adopt a range of different strategies (Christiansen et al, 2017), and there was a risk that dealing with patients' relatives could be perceived a stressful task in itself (Aadal et al, 2018) that shifts focus away from the patient.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, healthcare professionals were found to need a wide range of interaction skills to support interactions with both patients and the family members and carers of patients, who can play key roles in the patient's care and rehabilitation. Aadal et al (2018) argued that successful rehabilitation requires family members and the patient to be treated as a unit. Therefore, healthcare professionals must possess a holistic awareness of the patient's situation and have the competence to include the family by guiding them to understand their needs (Aadal et al, 2018; Theadom et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Aadal, Angel, Dreyer, Langhorn, and Pedersen (2013) expressed the need for consideration of patients' individualization and increased interdisciplinary teamwork in nursing practice. The role of nurses in supporting patients' relatives also needs to be addressed, as relatives are important in providing care post-discharge (Aadal, Angel, Langhorn, Pedersen, & Dreyer, 2018). Therefore, because nursing roles in stroke rehabilitation are multi-faceted, complicated, and constantly changing, nurses need to holistically engage in rehabilitation care.…”
mentioning
confidence: 99%
“…Involvement of relatives has become a much discussed area in the healthcare system, and relatives are often seen as a resource for both patient and health professionals (Aadal, Angel, Langhorn, Pedersen, & Dreyer, 2017;Angel, 2015). Consideration about relatives' actual ability to take responsibility must be prioritised, and health professionals must constantly be aware of relatives' own needs for support (Wallengren, Friberg, & Segesten, 2008 …”
Section: Several Studies Confirm That Relatives Need Information Aboutmentioning
confidence: 99%